Ψ-Stability of Nonlinear Volterra Integro-Differential Systems with Time Delay - Lianzhong Li; Maoan Han; Xin Xue; Yuanyuan Liu (Abstract and Applied Analysis)
We give some sufficient conditions for Ψ-uniform stability of the trivial solutions of a nonlinear differential system and of nonlinear Volterra integro-differential systems with time delay.